The Effect of Using Liveworksheet On Students’ Activeness And Vocabulary Mastery In Mts Masmur Pekanbaru - Ingriyani, Megy; Hasibuan, Kalayo; Zulhiddah, Zulhiddah (Innovative: Journal Of Social Science Research, 2025)
This research was aimed to find out the significant effect of using liveworksheet on students’ activeness and vocabulary mastery. This research was a quasi-experimental one group design pre-test and post-test group design. The participant of this research was 20 students. This study was conducted at Mts Masmur Pekanbaru. The findings of this research were; first, there was a significance effect of the students’ activeness by using live worksheet at grade eight of MTS Masmur Pekanbaru. It found that the value sig. (0.50 and .64) was higher than 0.05. Second, there was a significant effect of using liveworksheet on students’ vocabulary mastery in learning english. It was obtained that the value of (0.82 and .82) was higher than 0.05.  Also, the mean score in the pre test 77.80 and post-test was 84.05. By comparing the mean score above, it can be seen that the score was more higher increased to enhance the students’ vocabulary mastery. In addition, the use of liveworksheet was significantly effective at Moderate Effect category on the students’ activeness at grade eight of Mts Masmur Pekanbaru. The use media in learning vocabulary mastery which the English teacher usually 0.825 > 0.625. Last, it proved that both of the students’ activeness and vocabulary mastery were improved because the sig (2 -tailed) of the data is lower than 0.05. it means that there is a significant effect before and after on students’ activeness and vocabulary mastery by using Liveworksheet website.